2002
DOI: 10.1136/gut.51.6.818
|View full text |Cite
|
Sign up to set email alerts
|

Colonic epithelial cells are a major site of macrophage inflammatory protein 3alpha (MIP-3alpha) production in normal colon and inflammatory bowel disease

Abstract: Background and aim: Macrophage inflammatory protein 3α (MIP-3α) is a recently described lymphocyte directed C-C chemokine expressed predominately at extralymphoid sites, including the intestine. The aim of this study was to determine whether colonic epithelial cells produce MIP-3α and whether its expression is upregulated in inflammatory bowel disease. Methods and results: We found that interleukin 1β and tumour necrosis factor α dose dependently stimulated MIP-3α production in Caco-2 and HT-29 intestinal epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 47 publications
5
104
2
2
Order By: Relevance
“…This stimulus was selected because colonic levels of this pro-inflammatory cytokine are significantly elevated in human IBD (28). Furthermore, we have shown previously that IL-1␤ can dose-dependently upregulate MIP-3␣ mRNA and protein production in Caco-2 colonic epithelial cells (15).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This stimulus was selected because colonic levels of this pro-inflammatory cytokine are significantly elevated in human IBD (28). Furthermore, we have shown previously that IL-1␤ can dose-dependently upregulate MIP-3␣ mRNA and protein production in Caco-2 colonic epithelial cells (15).…”
Section: Methodsmentioning
confidence: 99%
“…Promoter Region-Recent studies from our laboratory have shown that enterocytes are a major site of MIP-3␣ production in human colon and that epithelial MIP-3␣ protein levels are elevated in IBD (15). However, the molecular mechanisms that control MIP-3␣ gene expression in intestinal epithelial cells are poorly understood.…”
Section: Cloning and Analysis Of The Human Mip-3␣mentioning
confidence: 99%
See 2 more Smart Citations
“…1 It is well known that CCL20 can be produced by intestinal epithelial cells, particularly in response to stress. 2,3 CCL20-CCR6 interactions have recently been shown to be instrumental in intestinal tumorigenesis and colorectal cancer growth. [4][5][6] While the direct role of CCL20-CCR6 interactions on promoting malignant behavior in neoplastic colon cancer cells has been well demonstrated, [6][7][8] despite the fact that chemokines are most known for their effects on immune cells, the role of these interactions on immune cells in colon cancer stroma has not been well studied.…”
Section: Introductionmentioning
confidence: 99%